A Child on Crossroad of Two Isolated Worlds - Afaf Manzoor (UMT Education Review, 2018)
An ever-increasing focus on out-of-school children may bring a new challenge to the already shaky system of schooling in Pakistan. A sustained segregatory and exclusionary way of thinking even at the highest ministerial level has given birth to two separate worlds; general education and special education. The habitat of both worlds follows different sets of beliefs about education, children, teaching and learning, pedagogy and assessment. The interaction between these communities has remained sorrowfully minimal. As the push to enroll every child in school with a target of “No child left behind” has increased, it has become even more difficult for parents and families to choose an appropriate school for children with disabilities. Often, the closest mainstream school treats them as aliens, whereas an alternative or special school may be up to 12km away from the child leaving few or no option for parents to send their children with disabilities to school. As the Punjab government has taken a forward step for inclusive education in two districts, it has become more obvious that there are many challenges in creating realistic accommodations for children with special needs in “mainstream schools”. This concept paper has explored the gaps both in theory and practice that may hinder the inclusion of all children in their neighborhood schools.